2000
DOI: 10.1017/s1368980000000094
|View full text |Cite
|
Sign up to set email alerts
|

Short stature and hypertension in the city of Rio de Janeiro, Brazil

Abstract: Objective: Stature is a powerful indicator of poor nutrition early in life in nations where undernutrition is a public health problem. Hypertension in adults has been associated with factors present early in life such as low birth weight. We tested the hypothesis that short stature is associated with hypertension among adults. Design and setting: A household survey of representative adults in Rio de Janeiro city, Brazil was carried out in 1996. Subjects: Blood pressure and anthropometric measures were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 28 publications
2
22
0
3
Order By: Relevance
“…Possible reasons for the lack of an association between birthweight and blood pressure include the strong correlation between blood pressure and adult BMI negating any influences of the early-life environment. As observed by Schieri et al, our study did not show any association between the short obese and adult variables compared to tall obese (27).…”
Section: Discussionsupporting
confidence: 73%
“…Possible reasons for the lack of an association between birthweight and blood pressure include the strong correlation between blood pressure and adult BMI negating any influences of the early-life environment. As observed by Schieri et al, our study did not show any association between the short obese and adult variables compared to tall obese (27).…”
Section: Discussionsupporting
confidence: 73%
“…Mortality rate increase in those states may have been influenced by: 1) improved diagnosis for the cause of death; 2) the results from higher urbanization level; 3) worse social and economic conditions in the region; 4) low schooling; and 5) other reasons, still questionable, which include from body weight at birth 14 to nutritional 15 , cultural 16 , and behavioral 17 aspects. Worsened social and economic conditions, low urbanization level, and low schooloing are attractive hypotheses, since better living standards are associated to decreased risk of death due to CD [18][19][20] Statistical Analysis -Multiple linear regression model was used.…”
Section: Discussionmentioning
confidence: 99%
“…Data from studies in Brazil from others and us revealed an association between short stature and obesity in women, but not in men (Velasquez-Melendez et al, 1999;Sichieri et al, 2000;Florêncio et al, 2001). Studying the nutritional status of 1247 individuals of a community, living in the outskirts of Maceió (northeastern Brazil), a high prevalence of overweight-obesity (25%) and stunting (22%) was found.…”
Section: Introductionmentioning
confidence: 87%